0511 Upper Airway Stimulation For Obstructive Sleep Apnea: A Single Center Clinical Experience With 100 Patients. (27th April 2018) - Heiser, C; Wirth, M; Hofauer, B
Abstract: Introduction: Upper airway stimulation (UAS) is a novel therapy for patients with obstructive sleep apnea (OSA). The aim of this study was to analyze the application and outcome of UAS in patients with moderate to severe OSA in the clinical routine of a tertiary referral center. Methods: One hundred patients who received a UAS device (Inspire Medical Systems) were included. Treatment outcome was evaluated at 2, 3, 6, 12, 24 and 36 months after surgery. Data collection included demographics, body mass index (BMI), apnea hypopnea index (AHI), oxygen saturation and desaturation index (ODI), Epworth Sleepiness Score (ESS) and adherence to therapy. Results: The mean age was 58.7 years with 94 patients being male and 6 female. Mean BMI was 29.4kg/m 2 . The mean pre-implantation AHI of 36.7/h could be reduced to 6.9/h (12 months), to 6.8/h (24 months) and to 6.7/h (36 months) (p<0.001). The mean pre-implantation ODI of 34.4/h could be reduced to 8.0/h (12 months), to 12.0/h (24 months) and to 8.2/h (36 months) (p=0.004). The mean pre-implantation ESS of 11.0 could be reduced to 6.0 after 12, 24 and 36 months (p=0.006). Therapy adherence was a usage of 6.6 hours/night after 24 months and 6.3 hours/night after 36 months. Conclusion: OSA can be successfully treated with upper airway stimulation on a long-term outcome. Patients maintained high adherence to therapy use after 36 months. Upper airway stimulation has been successfully implemented in the routine clinical management of OSA outside of a clinical trial setting and should be offered to incompliant patients to CPAP, who met the inclusion criteria for implantation. Support (If Any): None.